# Solve for y 3(y-1)-2y+3=5y+4y+10

3(y-1)-2y+3=5y+4y+10
Simplify 3(y-1)-2y+3.
Simplify each term.
Apply the distributive property.
3y+3⋅-1-2y+3=5y+4y+10
Multiply 3 by -1.
3y-3-2y+3=5y+4y+10
3y-3-2y+3=5y+4y+10
Combine the opposite terms in 3y-3-2y+3.
3y-2y+0=5y+4y+10
3y-2y=5y+4y+10
3y-2y=5y+4y+10
Subtract 2y from 3y.
y=5y+4y+10
y=5y+4y+10
y=5y+4y+10
y=9y+10
Move all terms containing y to the left side of the equation.
Subtract 9y from both sides of the equation.
y-9y=10
Subtract 9y from y.
-8y=10
-8y=10
Divide each term by -8 and simplify.
Divide each term in -8y=10 by -8.
-8y-8=10-8
Cancel the common factor of -8.
Cancel the common factor.
-8y-8=10-8
Divide y by 1.
y=10-8
y=10-8
Simplify 10-8.
Cancel the common factor of 10 and -8.
Factor 2 out of 10.
y=2(5)-8
Cancel the common factors.
Factor 2 out of -8.
y=2⋅52⋅-4
Cancel the common factor.
y=2⋅52⋅-4
Rewrite the expression.
y=5-4
y=5-4
y=5-4
Move the negative in front of the fraction.
y=-54
y=-54
y=-54
The result can be shown in multiple forms.
Exact Form:
y=-54
Decimal Form:
y=-1.25
Mixed Number Form:
y=-114
Solve for y 3(y-1)-2y+3=5y+4y+10

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top